Linear algebra concepts with SageMath for systems engineering students - Ceron Bravo, Samin Ingrith; Romero Luna, Roxana María (Scientia et technica, 2023)
This work presents an innovative proposal for the teaching and learning of systems of linear equations, graphical interpretation in the plane, in space and orthogonal projection, in the subject of Linear Algebra, mediated by the SageMath software as a technology of learning and knowledge. The proposal was carried out in some Linear Algebra courses in the Systems Engineering career at the University of Cauca, helping to increase its quality, reduce the retention rate and contribute to educational innovation in the university student population. The methodology for the development of this work consisted of the design and application of activities that comprise a set of problems which require the creation of functions in the Python programming language under the SageMath, environment to obtain possible solutions and correlate algebraic and geometric representation registers of the mathematical objects necessary for its solution. We conclude at the end of this educational research the relevance of the integration of technological tools within the classroom in conjunction with active methodological strategies to stimulate the understanding of some concepts of Linear Algebra; since the student can visualize, manipulate and observe these abstract mathematical objects, eliminating unnecessary manual actions and focusing on the analysis of logical deduction for the solution of the proposed activities.